Reduced time for evaluation of the germination test for sunflower seeds - Carla Massimo Caldeira; Maria Laene Moreira de Carvalho; João Almir Oliveira; Verônica Yumi Kataoka; Ana Izabella Freire (Journal of Seed Science, 2015)
Establishing ideal conditions and speed in carrying out the germination test for sunflower seeds is of utmost importance in quality control programs of companies dedicated to the production of high technology seeds. In this regard, the aim of this study was to verify the possibility of reducing the evaluation time of the germination test of sunflower seeds in different substrates and temperatures. Six seed lots of the cultivar Helio 251 and six lots of the cultivar Helio 253 were used. As well as germination, determinations were made of first count germination and seed health. The seeds were kept in a germination chamber at 25 ºC, 30 ºC, and 20-30 ºC for the paper substrate, and 25 ºC and 30 ºC for the sand substrate. To verify the possibility of reducing the evaluation time of the germination test, the number of normal seedlings were counted daily, up to the tenth day after sowing. It was concluded that it is possible to conclude the germination test on the seventh day after sowing in sand at the temperature of 25 °C.